A Pre-Adolescent and Adolescent Clinical Sample Study about Suicidal Ideation, Suicide Attempt, and Self-Harming - Alessia Raffagnato; Sara Iannattone; Rachele Fasolato; Elisa Parolin; Benedetta Ravaglia; Gaia Biscalchin; Annalisa Traverso; Silvia Zanato; Marina Miscioscia; Michela Gatta (MDPI AG, 2022)
Suicide is the second cause of death among adolescents, and nonsuicidal self-injury (NSSI) is one of the main risk factors for suicidal behavior. However, the possible variables specifically associated with suicidal ideation and suicide attempt, as well as the psychopathological characteristics linked to the concomitant presence of suicidal ideation/attempt and NSSI are still under-investigated in youth. The current study aimed to address these issues in a sample of 174 young Italian inpatients (Mage = 14.3 years ± 1.93, 78.2% girls). Sociodemographic and clinical variables were assessed through psycho-diagnostic interviews and ad hoc questionnaires. A binomial logistic regression was performed to identify the predictors of suicidal ideation and suicide attempt. Then, Kruskal-Wallis tests were run to analyze the psychopathological differences between patients with suicidal ideation and suicide attempt considering the coexistence of NSSI. The results highlighted that previous access to child mental health services and general psychopathological problems significantly predicted suicidal ideation, while previous hospitalizations, borderline personality functioning, and affective disorders significantly predicted suicide attempt. In general, inpatients with also NSSI reported higher levels of internalizing, somatic and total problems, impulsiveness, alexithymia, and emotional dysregulation. The clinical implications of our findings in terms of primary and secondary preventive programs are discussed.